Rola muzyki współczesnej w kształceniu pianistycznym - wybrane aspekty zagadnienia = The role of contemporary music in piano education - selected aspects - Różański, Piotr (Zielona Góra ; Skarbona: Stowarzyszenie Polskich Muzyków Kameralistów)
Contemporary music is an underestimated but exceptionally valuable element of piano education. Its stylistic diversity implies the necessity to develop a substantial flexibility of playing skills. The performer ? while expanding traditional pianistic "values" present in earlier repertoire ? must face new challenges: realization of serial structures in which each parameter of the sound is precisely defined; a factual co-creating of an artistic opus in aleatoric forms but also in genres like happening or instrumental theatre; the skill of effective but safe preparation of the instrument; heterogeneity of a music notation (i.a. graphic score).
Keywords: muzyka współczesna; kształcenie pianistyczne; contemporary music; piano education